Microenvironment changes in arteriovenous malformations after stereotactic radiation - Ung, Timothy H.; Belanger, Katherine; Hashmi, Ayesha; Sekar, Vashisht; Meola, Antonio; Chang, Steven D. (Frontiers in Human Neuroscience, 2022)
Cerebral arteriovenous malformations are dysplastic vascular tangles with aberrant vascular dynamics and can result significant morbidity and mortality. A myriad of challenges are encountered when treating these lesions and are largely based on nidal size, location, and prior hemorrhage. Currently, stereotactic radiosurgery is an accepted form of treatment for small to medium sized lesions and is especially useful in the treatment of lesions in non-surgically assessable eloquent areas of the brain. Despite overall high rates of nidal obliteration, there is relatively limited understand on the mechanisms that drive the inflammatory and obliterative pathways observed after treatment with stereotactic radiosurgery. This review provides an overview of arteriovenous malformations with respect to stereotactic radiosurgery and the current understanding of the mechanisms that lead to nidal obliteration.